2021
DOI: 10.3390/biomedicines9121812
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomics and Lipidomics Integration in Alzheimer Disease: Pathways Involved in Early Stages

Abstract: Background: Alzheimer Disease (AD) is the most prevalent dementia. However, the physiopathological mechanisms involved in its development are unclear. In this sense, a multi-omics approach could provide some progress. Methods: Epigenomic and lipidomic analysis were carried out in plasma samples from patients with mild cognitive impairment (MCI) due to AD (n = 22), and healthy controls (n = 5). Then, omics integration between microRNAs (miRNAs) and lipids was performed by Sparse Partial Least Squares (s-PLS) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 45 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Lipid peroxidation, caused by oxidative stress, is one of the most-studied markers of disease, and various molecules have been proposed as potential circulating biomarkers (See Section 3.5 Oxidative Stress ) [ 166 , 167 , 182 , 305 , 306 , 307 ]. Concerning fatty acids, dysregulation in their profile is linked to increased risk of dementia, with hexacosanoid acid (C26:0) being the most upregulated both in plasma and red blood cells of AD patients [ 303 , 308 , 309 ]. A correlation between the primary fatty acid amide level in plasma and Aβ pathology, hippocampal volume, and cognitive score was also reported [ 310 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lipid peroxidation, caused by oxidative stress, is one of the most-studied markers of disease, and various molecules have been proposed as potential circulating biomarkers (See Section 3.5 Oxidative Stress ) [ 166 , 167 , 182 , 305 , 306 , 307 ]. Concerning fatty acids, dysregulation in their profile is linked to increased risk of dementia, with hexacosanoid acid (C26:0) being the most upregulated both in plasma and red blood cells of AD patients [ 303 , 308 , 309 ]. A correlation between the primary fatty acid amide level in plasma and Aβ pathology, hippocampal volume, and cognitive score was also reported [ 310 ].…”
Section: Resultsmentioning
confidence: 99%
“… Jaouen and Gascon (2016) described miR-33 function modulating ATP-binding cassette transporter A1 (ABCA1) and interfering with Aβ plaque formation through cholesterol metabolism regulation. Peña-Bautista et al (2021) found hsa-miR-421 showed a positive correlation with some detected lipids (FA (16:0), FA (20:2), FA (18:2), FA (20:4), FA (20:3), FA (18:0), FA (14:0)) in AD plasma samples. Docosahexaenoic acids (DHA) are known to be beneficial in AD.…”
Section: Rna N6-methyladenosine Methylation In Alzheimer’s Diseasementioning
confidence: 80%
“…Several genetic strategies have been carried out in recent years to facilitate the identification of molecular players in AD. GWASs [ 17 , 46 ], targeted polygenic studies [ 47 , 48 ], multiomic strategies [ 49 ], and even genetic pleiotropy approaches have been performed [ 16 ], and a strong relationship between circulating lipids and genetic factors related to AD has been described [ 47 ]. However, other studies have found no conclusive relationship between lipids and AD using Mendelian randomization [ 50 ]; therefore, this is a topic that still requires attention.…”
Section: Discussionmentioning
confidence: 99%